ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2021) - Reza Panjaitan, Dinny; Sihombing, Halomoan; Harefa, Meilinda (Jurnal Akuntansi Nommensen, 2022)
This study aims to analyze the effect of profitability, leverage, inventory intensity, and fixed asset intensity on tax management in manufacturing companies in the food and beverage sub-sector for the period 2018-2021. The population used was 36 companies and the samples taken were 19 companies with purposive sampling technique. The data used in this study are secondary data derived from the company's financial statements. The analysis method used is multiple linear regression analysis and data processing is carried out using SPSS software. The results showed that profitability has a negative effect on tax management, leverage has a positive effect on tax management, inventory intensity has a positive effect on tax management, and fixed asset intensity has a negative effect on tax management. The coefficient of determination test results shows that the independent variables (profitability, leverage, inventory intensity, and fixed asset intensity) are able to explain 77.4% of the variation in the dependent variable (tax management). This research has practical implications for companies to consider factors that influence tax management in decision making and corporate strategy.